Coumarins in traditional medicine: Bridging ancient wisdom and scientific progress - Yasser Fakri Mustafa (Phytomedicine Plus)
Coumarins are a diverse group of naturally occurring compounds long recognized in traditional medicine for their broad therapeutic potential. This narrative review explores their journey from ancient healing traditions—such as Ayurveda, Traditional Chinese Medicine, and various indigenous systems—to their contemporary biomedical relevance. Widely distributed in medicinal plants, coumarins have historically been used to treat inflammation, microbial infections, and oxidative stress-related conditions. These traditional applications are increasingly supported by modern pharmacological evidence. Structurally, coumarins exhibit significant chemical diversity, enabling a wide range of bioactivities, including anti-inflammatory, antioxidant, antimicrobial, and anticoagulant effects. Moreover, this review highlights how ancient practices effectively utilized these bioactive properties, many of which are now validated through experimental and clinical studies. On the other hand, advances in extraction methods, synthetic modifications, and drug delivery systems have improved the pharmacokinetic profiles and expanded the potential uses of coumarins. Despite their promise, safety concerns, particularly hepatotoxicity and dose-dependent effects, must be addressed to ensure clinical relevance. While natural coumarins generally display a favorable therapeutic index, synthetic derivatives require careful evaluation. Finally, this review aims to systematically explore the historical applications, pharmacological relevance, and therapeutic integration of coumarins in traditional medicine, while addressing their potential translational value in modern pharmacology. Bridging ethnopharmacological wisdom with contemporary science, coumarins emerge as promising candidates for integrative drug development. Their potential roles in treating neglected diseases and interacting synergistically with other agents warrant further exploration.